2008
DOI: 10.1007/s10334-008-0146-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiproject–multicenter evaluation of automatic brain tumor classification by magnetic resonance spectroscopy

Abstract: Justification Automatic brain tumor classification by MRS has been under development for more than a decade. Nonetheless, to our knowledge, there are no published evaluations of predictive models with unseen cases that are subsequently acquired in different centers. The multicenter eTUMOUR project (2004)(2005)(2006)(2007)(2008)(2009), which builds upon previous expertise from the INTERPRET project (2000INTERPRET project ( -2002 has allowed such an evaluation to take place. Materials and Methods A total of 253 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
147
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(157 citation statements)
references
References 53 publications
(77 reference statements)
10
147
0
Order By: Relevance
“…Moreover, lower classification rates (60-F o r P e e r R e v i e w 6 80%) or <0.8 average AUC were reported to distinguish GBM and MET in other previous studies (13,14,16,17,(22)(23)(24)(25).…”
mentioning
confidence: 74%
“…Moreover, lower classification rates (60-F o r P e e r R e v i e w 6 80%) or <0.8 average AUC were reported to distinguish GBM and MET in other previous studies (13,14,16,17,(22)(23)(24)(25).…”
mentioning
confidence: 74%
“…45,46 The explanation is that the superior limit of the voxel was close to the skull (see the brain circumvolutions), where contamination from subcutaneous fat was likely classification techniques. 43 Despite the fact that classes sometimes have overlapping spectra, linear and nonlinear classifiers usually perform similarly 44 for these types of discriminations. While this may seem disappointing for PR practitioners, it has an interesting corollary: spectra that are consistently misclassified by different PR techniques will be, most probably, outliers ( Figure 5).…”
Section: Lessons Learned From Previous Studiesmentioning
confidence: 99%
“…94 1 H MRS has also been used to identify the most active regions of large complex tumors thereby aiding tumor biopsy 95,96 and for delineating tumor margins which can extend beyond the enhancing regions seen on conventional MRI. 95 The entire MRS profile has been shown to be a strong characteristic of tumor type and has been studied extensively as an aid to non-invasive diagnosis, the best results coming from the use of pattern recognition [97][98][99][100] Large multi-center studies have shown that this can be robust even when evaluated prospectively 101 and clinical decision support systems based on MRS have been developed. 102,103 High total choline and mobile lipids together with low myo-inositol (for an example brain tumor 1 H MRS see Fig.…”
Section: Multinuclear Mrs For Cancer Imagingmentioning
confidence: 99%